2015
DOI: 10.3389/fpsyg.2015.01717
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Factors on Sleep Patterns and School Performance in Adolescents

Abstract: Background: Modern life, with its many distractions, is seeing sleep quantity and quality decline during adolescence. This is a concern as research persuasively demonstrates the negative impact of reduced sleep on academic achievement, both in terms of learning and behavior.Aims: This study examined the relationship between sleep and school functioning in adolescence, with a focus on environmental factors that might mediate this relationship.Sample and Method: Forty-seven adolescents took part. Sleep was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 58 publications
(81 reference statements)
4
49
1
6
Order By: Relevance
“…Overall, these studies suggest that use of technology does adversely impact sleep duration. Ten of the included studies measured bedtime/nighttime media use using various methods, mainly self‐report or parent‐report, and either asked parents or youth to report on the amount of time using screen media before going to bed, or asked if any screens were present in the youth's bedroom (Arora, Broglia, Thomas, & Taheri, ; Dimitriou, Knight, & Milton, ; Dube, Khan, Loehr, Chu, & Veugelers, ; Lemola, Perkinson‐Gloor, Brand, Dewald‐Kaufmann, & Grob, ; Munezawa et al, ; Nathanson & Beyens, , ; Oshima et al, ; Scott & Woods, ; Seo, Kim, Yang, & Hong, ). All studies that focused on nighttime use specifically found that social media, tablet, or smartphone use was associated with shorter sleep duration.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these studies suggest that use of technology does adversely impact sleep duration. Ten of the included studies measured bedtime/nighttime media use using various methods, mainly self‐report or parent‐report, and either asked parents or youth to report on the amount of time using screen media before going to bed, or asked if any screens were present in the youth's bedroom (Arora, Broglia, Thomas, & Taheri, ; Dimitriou, Knight, & Milton, ; Dube, Khan, Loehr, Chu, & Veugelers, ; Lemola, Perkinson‐Gloor, Brand, Dewald‐Kaufmann, & Grob, ; Munezawa et al, ; Nathanson & Beyens, , ; Oshima et al, ; Scott & Woods, ; Seo, Kim, Yang, & Hong, ). All studies that focused on nighttime use specifically found that social media, tablet, or smartphone use was associated with shorter sleep duration.…”
Section: Resultsmentioning
confidence: 99%
“…Dagmara Dimitriou, et al [2] in their study have stated that stimulant consumption and gadget usage before going to bed decreases the number of sleeping hours and hampers the quality of sleep. They also stated that decreased sleep can attributed as one of the causes of hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…Sleep is a condition of body and mind which typically recurs for several hours every night, in which the nervous system is inactive, the eyes are closed, the posture muscles relaxed, and consciousness practically suspended [1]. Blood pressure is the pressure of blood in the circulatory system, often measured for diagnosis since it is closely related to the force and rate of the heart beat and the diameter and elasticity of the arterial walls [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nadalje, roditeljski nadzor se smanjuje u brojnim aspektima života mlade osobe, pa tako i nad vremenom odlaska na spavanje i načinom provođenja vremena prije spavanja (5,7). Nemali broj adolescenata do kasnih noćnih sati provodi vrijeme na internetu ili čak ostavljaju tijekom noći uključen mobitel kako bi u svakom trenutku bili dostupni vršnjacima (12), a istraživači naglašavaju da upravo gledanje TV-a i socijalno druženje na internetu neposredno prije spavanja može povećati fiziološku pobuđenost i otežati uspavljivanje (24).…”
Section: Discussionunclassified
“…Furthermore, parental supervision is reduced in many aspects of life of the young person and thus also in the control of bedtime and the time spent before it (5,7). A large number of adolescents spend late night hours on the Internet or even leave their cell phones turned on during the night to be available at all times (12), and researchers point out that watching television and socializing on the Internet before bed can increase psychological arousal and cause sleep difficulties (24).…”
Section: Discussionmentioning
confidence: 99%